PENENTUAN PRIORITAS PENANGANAN RUAS JALAN KABUPATEN DI KABUPATEN KLUNGKUNG DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - I Wayan Juniarta; Dewa Made Priyantha Wedagama; I Made Agus Ariawan (Master of Civil Engineering Program Study, Faculty of Engineering, Udayana University, 2021)
Budget limitations are a problem in road handling programming. The purpose of this study is to determine the hierarchical arrangement and quantitative measurements of each sub-criteria so that a mathematical formula is formed to develop a priority scale for handling district roads with the study location in Klungkung Regency. The decision making method used is Analytical Hierarchy Process (AHP). The hierarchical arrangement of the research results consisting of Level-1 is the objective, namely determining the priority scale for handling district roads in Klungkung Regency. Level-2 is a criterion, and Level-3 is a sub-criteria that affects the criteria. The criteria used are i). Network system (A) with sub-criteria for road conditions (A1), pavement width (A2) and disaster-prone areas (A3), ii). Land Use System (B) with sub-criteria for access to government offices (B1), to areas of tourist attraction (B2), to strategic transportation areas (B3), and to areas of holy places and cultural heritage (B4), iii). Movement System Criteria (C) with sub-criteria LHR (C1), and iv). Institutional System Criteria (D) with subcriteria included in the proposal in the Musrenbang (D1), according to the direction of RENSTRA (D2), and equal distribution of road stability (D3). The weights of each sub-criteria A1, A2, A3, B1, B2, B3, B4, C1, D1, D2, and D3 are 15.23%, 7.80%, 5.80%, 3.25%, respectively. 9.50%, 8.10%, 3.24%, 19.9%, 6.32%, 7.63%, and 13.24%. The mathematical formula based on the weight of the quantitative measurements, namely Y = 15.23A1 + 7.80A2 + 5.80A3 + 3.25B1 + 9.50B2 + 8.10B3 + 3,24B4 + 19.9C1 + 6,32D1 + 7,63D2 + 13 , 24D3. Obtained a priority scale arrangement of road handling, namely 62 very high priority scale roads, 58 high priority scale roads, 60 medium priority scale roads, 59 low priority scale roads, and 60 very low priority scale roads.